Human Relations in the Workplace - Rotemberg, Julio J. (Journal of Political Economy, 1994)
This paper seeks to understand what motivates workers to be altruistic toward one another and studies whether firms benefit from encouraging these "human relations" in the workplace. The paper first proposes that feelings of altruism can be individually rational in certain settings in which the variables controlled by the workers are strategically linked. The paper then studies what this implies for equilibrium altruism in two situations. The first has workers who are paid as a function of joint output. The second is the relationship between subordinates and their supervisors.